COPD management as a model for all chronic respiratory conditions: report of the 4th Consensus Conference in Respiratory Medicine - Nardini, Stefano; De Benedetto, Fernando; Sanguinetti, Claudio M.; Bellofiore, Salvatore; Carlone, Stefano; Privitera, Salvatore; Sagliocca, Luciano; Tupputi, Emmanuele (Multidisciplinary Respiratory Medicine, 2017)
Background: Non-communicable diseases (NCDs) kill 40 million people each year. The management of chronic respiratory NCDs such as chronic obstructive pulmonary disease (COPD) is particularly critical in Italy, where they are widespread and represent a heavy burden on healthcare resources. It is thus important to redefine the role and responsibility of respiratory specialists and their scientific societies, together with that of the whole healthcare system, in order to create a sustainable management of COPD, which could become a model for other chronic respiratory conditions. Methods: These issues were divided into four main topics (Training, Organization, Responsibilities, and Sustainability) and discussed at a Consensus Conference promoted by the Research Center of the Italian Respiratory Society held in Rome, Italy, 3–4 November 2016. Results and conclusions: Regarding training, important inadequacies emerged regarding specialist training - both the duration of practical training courses and teaching about chronic diseases like COPD. A better integration between university and teaching hospitals would improve the quality of specialization. A better organizational integration between hospital and specialists/general practitioners (GPs) in the local community is essential to improve the diagnostic and therapeutic pathways for chronic respiratory patients. Improving the care pathways is the joint responsibility of respiratory specialists, GPs, patients and their caregivers, and the healthcare system. The sustainability of the entire system depends on a better organization of the diagnostic-therapeutic pathways, in which also other stakeholders such as pharmacists and pharmaceutical companies can play an important role.